ISTERI SEBAGAI PENCARI NAFKAH UTAMA: Studi terhadap Perajin Kapuk di Desa Imogiri, Bantul, Yogyakarta - Djazimah, Siti; Habudin, Ihab (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2016)
Islam has expressly regulate the division of tasks and roles between husbands and wives fairly. Although the husband is obliged to provide sustenance for his wife and children, but the family law of Islam does not forbid a wife from helping her husband in making a living with her husband's consent and does not interfere with her obligations as a housewife. There is a wife in a family of craftsmen in the village of Tegal Kembang, Imogiri, Yogyakarta, which acts as the main breadwinners for their families. This article examines the wives who work as the wage earners by using the concept of maqa> s} id ash-shari'ah < 'ah. The impact that emerges of the role of the kapok craftsmen woman is more on the impacts that are in positive traits and it is associated with the hajjiy and daruriy needs. The wife who has an income has the economic independence power that can even sustain the needs of the family. Social interactions that occur in kapok craftsmen community, make a strong emotional connection between kapok craftsmen. While the social interaction with the "outside world" (consumers) clearly provides insight of the Kapok Craftsmen. As for the negative impact of the mother's role of Kapok craftsman towards parenting does not seem significant.[Islam secara tegas telah mengatur tentang pembagian tugas dan peran antara suami dan istri secara adil. Walaupun suami berkewajiban memberi nafkah kepada isteri dan anak-anaknya, tetapi hukum keluarga islam tidak melarang istri membantu suaminya dalam mencari nafkah dengan persetujuan suaminya dan tidak mengganggu kewajibannya sebagai seorang ibu rumah tangga. Ada istri pada keluarga perajin kapuk di dusun Tegal Kembang, Imogiri, Bantul,  Yogyakarta, yang berperan sebagai pencari nafkah utama bagi keluarganya. Tulisan ini mengkaji para isteri yang bekerja sebagai pencari nafkah dengan menggunakan konsep maqa>s}id asy-syari<‘ah. Dampak yang ditimbulkan dari peran yang dijalankan para ibu perajin kapuk adalah lebih pada dampak yang sifatnya positif dan hal ini terkait dengan kebutuhan yang sifatnya daruriy dan hajjiy. Para isteri yang mempunya penghasilan tersebut memiliki kemandirian dalam ekonomi bahkan dapat menopang kebutuhan keluarga. Interaksi sosial yang terjadi dalam komuitas perajin kapuk, menjadikan kuatnya hubungan emosional di antara perajin kapuk. Sementara  interaksi sosial dengan “dunia luar” (konsumen) jelas memberikan wawasan perajin kapuk semakin bertambah. Adapun dampak negatif peran ibu sebagai perajin kapuk terhadap pengasuhan anak tidak nampak secara signifikan.]